PERANG TARIF DALAM INDUSTRI LAYANAN JASA TELEPON SELULER: ANALISIS WACANA IKLAN OPERATOR TELEPON SELULER DI MEDIA MASSA - Syamsi, Kastam (Diksi, 2015)
As a product of media, advertisements in both print and electronic media with their hegemony are made to persuade readers or listeners to act as the advertisements wish, namely buying the advertised products. Based on an analysis of mass media, in advertisements by cellular phone operators, there is a price war as a strategy to attract consumers. Each cellular phone operator tries to show an image that the company offers the lowest price. This may influence and deceive consumers as the party that is forced to use the company’s service. In practice, an offer with a low price usually needs a condition and requirement that consumers have not known before. Therefore, it is necessary that consumers should be selective and critical in digesting an advertisement made by a cellular phone operator offering a low price. Keywords: advertisement, cellular phone operator, mass media